Experimental study of electromagnetic-assisted rare-earth doped yttrium iron garnet (YIG) nanofluids on wettability and interfacial tension alteration - Lau, Z.Y. (MDPI AG, 2019)
Applications of nanoparticles (NPs) in the Enhanced oil recovery (EOR) method has become a major research field as nanoparticles are found to be able to interfere with the interfacial tension and wettability of multiphase fluids within the reservoir formation with or without the irradiance of the electromagnetic (EM) waves. For future EOR usage, a material with high temperature stability and low losses under oscillating wave is recommended, Yttrium Iron Garnet (YIG). This paper describes the synthesis of rare-earth doped YIG (RE-YIG, RE = (Lanthanum (La), Neodymium (Nd) and Samarium (Sm)) and the roles of rare-earth in alteration of magnetic properties. These magnetic properties are believed to have direct relation with the change in wettability, viscosity and interfacial tension of YIG nanofluids. Here we prepared the Y2.8R0.2Fe5O12 (R = La, Nd, Sm) NPs using the sol-gel auto-combustion technique and further annealed at 1000 Â°C for 3 h. The Field Emission Scanning Electron Microscope (FESEM) images reveal the particles having grain size ranging from 100-200 nm with high crystallinity and X-ray Powder Diffraction (XRD) shows varying shift of the peak position due to the bigger size of the rare-earth ions which resulted in structural distortion. The wettability of the nanofluid for all samples shows overall reduction under the influence of EM waves. On the other hand, the interfacial tension (IFT) and viscosity of RE-YIG nanofluids has lower value than the pure YIG nanofluids and decreases when the ionic radius of rare-earth decreases. Sm-YIG has the highest magnitude in IFT and magnetization saturation of 23.54 emu/g which suggests the increase in magnetization might contribute to higher surface tension of oil-nanofluid interface. Â© 2019 by the authors.